Routledge handbook of Asian regionalism - Beeson, Mark; Stubbs, Richard (Routledge, 2012)
"The Routledge handbook of Asian regionalism is a definitive introduction to, and analysis of, the development of regionalism in Asia, including coverage of East Asia, Southeast Asia and South Asia. The contributors engage in a comprehensive exploration of what is arguably the most dynamic and important region in the world. Significantly, this volume addresses the multiple manifestations of regionalism in Asia and is consequently organised thematically under the headings of: - conceptualizing the region - economic issues - political issues - strategic issues - regional organizations. As such, the handbook presents some of the key elements of the competing interpretations of this important and highly contested topic, giving the reader a chance to evaluate not just where Asian regionalism is going but also how the scholarship on Asian regionalism is analysing these trends and events."--Publisher's description.